Advocating of parties in administrative disputes - Lončar, Zoran (Zbornik radova Pravnog fakulteta u Novom Sadu, 2016)
The introduction in administrative dispute a new rule, that the court in this type of legal dispute, decides on the basis of the facts established on oral and public hearing, in significant degree extent the topical issue of representation in the administrative dispute. During the first few years in work of newestablished Administrative Court in Republic of Serbia, jurisprudence was completely corresponded to all legal rules in advocating of the parties in this type of dispute. However, with the gradualy increasing number of oral hearings, which are still, unfortunately, exception rather than rule, we notice the existence of a certain deviation from the legal rules, which is reflected in giving opportunities Attorney’s Office to represent the defendant authority as a party to the hearing, although when the subject of dispute is not violation of any property rights of the state, autonomous province or local self-government, which is primary competence of Attorney’s Office. The main problem in this occurrence is that the point of representation of organs, as decision making authorities, by Attorney’s Office, is in a greater protection of property interests of territorial communities, but on this way, it is only creating additional costs of an administrative dispute, which in the case of loss of the dispute, falling on the burden of the citizens as a prosecutor, and go directly to the budget of the relevant territorial community. Therefore, in order to create legal certainty and the protection of citizens property interests, it is necessary to discontinue with this practice and representation of the parties in this type of disputes start to exercise according to legal rules, which for the competent Attorney’s Office provide opportunity to participate in any administrative dispute when it considers that some administrative act violated property rights and interests of some of territorial communities.